LINC01133 contributes to the malignant phenotypes of non-small cell lung cancer by targeting miR-30b-5p/FOXA1 pathway: LINC01133 promotes NSCLC via miR-30b-5p/FOXA1 - Xin, Xiangbing; Liu, Yongshi; Li, Yan; Ji, Xiang; Yun, Yuhui; Yang, Guang; Liu, Honggang; Liang, Xiaohua; Yang, Sanhu (Cellular and Molecular Biology, 2024)
This study aimed to explore the mechanism of action of LINC01133 in non-small cell lung cancer. LINC01133 expression in NSCLC patient tissues and cells was detected by qRT-PCR. After transfecting siRNA-LINC01133 in NSCLC cells, the proliferation and invasive migration ability of the cells were assessed via CCK-8 and Transwell assay, respectively. The sublocalization of LINC01133 in NSCLC cells was analyzed by bioinformatics prediction and nucleoplasm separation assay and RNA-FISH assay. Analysis of the binding relationship between LINC01133, FOXA1 and miR-30b-5p was all through bioinformatics website analysis, dual-luciferase reporter and RNA Pulldown assay. Functional rescue experiments confirmed the character of miR-30b-5p and FOXA1 in LINC01133 regulating the NSCLC cells biological behavior. LINC01133 high expressions were found in NSCLC tissues and cells. siRNA-LINC01133 treatment inhibited NSCLC cells malignant behavior. Mechanistically: LINC01133 promoted FOXA1 expression through adsorption binding of miR-30b-5p. Knocking down miR-30b-5p expression or up-regulating FOXA1 expression was able to reverse siRNA-LINC01133 inhibitory effect of tumor cell malignant behavior. LINC01133 promoted FOX1 expression by competitively binding miR-30b-5p, which attenuated the targeting inhibitory effect of miR-30b-5p on FOXA1 and ultimately promoted proliferation and invasive migration of NSCLC cells.